American heritage college thesaurus. - Houghton Mifflin Company (Boston : Houghton Mifflin, 2004)
"The American Heritage College Thesaurus offers writers a wide selection of synonyms, phrasal verbs, and idioms for precise expression and graceful turns of phrase. Each group of synonyms is preceded by a full and clearly-written definition so that the distinctions between synonym groups can be seen at a glance. Groups of synonyms are connected to related groups by easy-to-follow cross-references, allowing the reader to search more broadly in the vocabulary of English without losing the vital thread of meaning. Hundreds of synonym paragraphs explain the nuances of core synonyms - the words we tend to use most and need most to vary. Each synonym is illustrated with a sentence or a pertinent quotation."--BOOK JACKET.
Machine derived contents note: Table of Contents -- Editorial and Production Staff vi -- Introduction vii -- How to Use This Book ix -- Thesaurus 1.
Keywords: English language -- Synonyms and antonyms